BGC‐Argo Floats Observe Nitrate Injection and Spring Phytoplankton Increase in the Surface Layer of Levantine Sea (Eastern Mediterranean). Issue 8 (28th April 2021) - D'Ortenzio, F.; Taillandier, V.; Claustre, H.; Coppola, L.; Conan, P.; Dumas, F.; Durrieu du Madron, X.; Fourrier, M.; Gogou, A.; Karageorgis, A.; Lefevre, D.; Leymarie, E.; et al.
Abstract: In the eastern Mediterranean Sea, satellites have observed events of spring surface‐chlorophyll increase in the Rhodes Gyre region recurring intermittently. Few in situ biogeochemical data, however, exist to confirm their consistency, elucidate their seasonal characteristics, or discriminate among the possible drivers. During the year 2018, an array of BGC‐Argo floats was deployed in the region, collecting the first‐ever annual time series of in situ profiles of biogeochemical parameters in this area. Their observations demonstrated that nitrates, driven by mixed‐layer dynamics, were available at surface from December 2018 onwards and could have sustained phytoplankton growth. Phytoplankton accumulation at the surface was observed by satellite only in March 2019 when the mixed‐layer depth shoaled. These findings confirm that blooms occurring before the start of seasonal stratification are not easily recorded by satellite observations and reaffirm the need to consolidate the BGC‐Argo network to establish time series of the evolution of biogeochemical processes. Plain Language Summary: The Levantine Sea, the easternmost area of Mediterranean Sea, is considered one of the poorest oceans on the Earth in terms of abundance of phytoplankton, the microscopic organisms that fuel the marine food web. However, historical data and satellite maps of chlorophyll (the pigment that reveals phytoplankton presence in the water) show episodic increases in the concentration of this pigment in the area near the island of Rhodes. To elucidate the characteristics of these events, a set of six robotic instruments ( i.e . the BGC‐Argo floats) was deployed in the Levantine Sea in 2018. A BGC‐Argo float is an autonomous, free‐floating instrument that makes oceanic observations over the first 2, 000 m of the water column on a regular basis. This article presents an analysis of the data collected by these six robots. They provided the very first annual time series of biogeochemical observations in area, including during winter, when ship and satellite data are hard to collect. Our results reveal the increase in phytoplankton occurring before the start of seasonal stratification, increase that is not easily recorded by satellite observations and reaffirm the need to consolidate the BGC‐Argo network to establish time series of the evolution of biogeochemical processes. Key Points: BGC‐Argo floats observe nitrate injections in surface Mediterranean waters Mixed‐layer dynamics sustain phytoplankton persistence all over winter‐very early spring The Mediterranean BGC‐Argo network provides unique observations that complement ship‐based sampling and satellite monitoring